Defining Deep‐Subwavelength‐Resolution, Wide‐Color‐Gamut, and Large‐Viewing‐Angle Flexible Subtractive Colors with an Ultrathin Asymmetric Fabry–Perot Lossy Cavity. Issue 23 (20th September 2019) - Zhao, Jiancun; Qiu, Meng; Yu, Xiaochang; Yang, Xiaoming; Jin, Wei; Lei, Dangyuan; Yu, Yiting
Abstract: Achieving structural colors with wide color gamut, large viewing angle, and high resolution remains practically challenging. Here, proposed is an asymmetric Fabry–Perot (F–P) lossy cavity to realize subtractive colors, simultaneously featuring wide gamut, angle insensitivity, high resolution, and good flexibility. The experimental results demonstrate that the realized structural colors are insensitive to the viewing angle up to ±60°, arising from the negligible light propagation phase shift in the ultrathin lossy cavity made of an amorphous silicon (a‐Si) layer; they also exhibit a wide color gamut covering the whole cyan, magenta, and yellow (CMY) color system, simply achieved through changing the thicknesses of the top metal layer and the middle lossy a‐Si layer. The ultrathin configuration enables printing such colors at a deep‐subwavelength resolution, and the ease of experimental fabrication enables their implementation on soft substrates. Accordingly, a 2D sketched image is printed using this cavity at a resolution of 150 000 dots per inch (dpi) in the geometrical space, corresponding to a minimum color pixel of 160 nm, well beyond the diffraction limit; a flexible structural color membrane with wide color gamut and large viewing angle is well adhered on an airplane model with a complex surface profile. Abstract : A subtractive structural color with a deep‐subwavelength resolution generated by an ultrathin asymmetric Fabry–Perot lossy cavity (Ag/amorphous silicon/Al) is proposed to realize wide color gamut, large viewing angle, and good flexibility. The ultrathin configuration enables printing such colors at a deep‐subwavelength resolution, and the ease of experimental fabrication enables their implementation on soft substrates.